Chronic HIV infection affects the expression of the 2 transcription factors required for CD8 T-cell differentiation into cytolytic effectors. - Ribeiro-dos-Santos, P; Turnbull, E; Monteiro, M; Legrand, A; Conrod, K; Baalwa, J; Pellegrino, P; Shaw, G; Williams, I; Borrow, P; Rocha, B (2012)
CD8 T cells lose the capacity to control HIV infection, but the extent of the impairment of CD8 T-cell functions and the mechanisms that underlie it remain controversial. Here we report an extensive ex vivo analysis of HIV-specific CD8 T cells, covering the expression of 16 different molecules involved in CD8 function or differentiation. This approach gave remarkably homogeneous readouts in different donors and showed that CD8 dysfunction in chronic HIV infection was much more severe than described previously: some Ifng transcription was observed, but most cells lost the expression of all cytolytic molecules and Eomesodermin and T-bet by chronic infection. These results reveal a cellular mechanism explaining the dysfunction of CD8 T cells during chronic HIV infection, as CD8 T cells are known to maintain some functionality when either of these transcription factors is present, but to lose all cytotoxic activity when both are not expressed. Surprisingly, they also show that chronic HIV and lymphocytic choriomeningitis virus infections have a very different impact on fundamental T-cell functions, "exhausted" lymphocytic choriomeningitis virus-specific cells losing the capacity to secrete IFN-γ but maintaining some cytotoxic activity as granzyme B and FasL are overexpressed and, while down-regulating T-bet, up-regulating Eomesodermin expression.